Collaborative Governance Process in Likupang Tourism Development In North Minahasa Regency - Pombengi, Jericho Danga; Posumah, Johny Hanny; Rorong, Arie Junus; Liando, Daud Markus (Jurnal Manajemen Pelayanan Publik, 2026)
Developing tourism as a strategic regional sector requires effective and collaborative governance to ensure sustainability, accountability, and equitable distribution of benefits for stakeholders. Likupang tourism is being developed through the involvement of various actors, from the government and the private sector to the local community, thus necessitating coordinated collaborative governance. The research aims to analyze the collaborative governance process in Likupang tourism development. Qualitative research was the methodology employed. The primary source of information is organized interviews, where the interviewer determines the problems and questions to ask themselves. The findings showed that the community's and resort owners' cooperation, namely with regard to waste management and the use of communal plantation land, was not optimal. The lack of international-caliber restaurants and souvenir shops, as well as the road access to Likupang. Through direct communication, the actors involved in tourist development engage in a collaborative process that fosters trust, strengthens commitment, and unites ideas and shared objectives. The collaborative governance process in Likupang tourism development occurred only at the face-to-face dialogue stage, while the stage of building trust, capacity, and commitment to unite perspectives is not optimal.